The soils of mountainous territories (in the Russian ) - T. V. Ananko; M. I. Gerasimova; D. E. Konyushkov (Бюллетень Почвенного института им. В.В. Докучаева, 2018)
Specific soils of mountainous regions having no analogues on plains occupy less than 3% of Russia. On the soil maps of Russian Federation (1 : 2.5 M scale, 1988), they are represented by 10 mapping units, the names of which, along with the term “mountainous” reflecting characteristic properties of these soils (general youth, thin profiles, high content of gravels, underlying by hard bedrock) contain information about the particular landscape conditions of soil formation. For updating of the map, the soils shown on it are renamed in agreement with the new Russian substantive-genetic soil classification system. The profile-genetic approach lying in the basis of this system excludes the use of landscape terms in soil names. The reclassification of mapping units is performed with due account for individual features of each particular polygon shown on the map. In essence, it consists of the search of information about the soil properties for identification of the diagnostic horizons and genetic properties of the soils to give formulae of their horizonation (in symbols of diagnostic horizons and properties). This search is based on the program and explanatory text to the map and various regional publications presenting information about the soils and the agents of soil formation. The formulae of the profiles are used to determine classification position of the soils in the substantive-genetic classification system. Most of the soils from this section of the legend belong to the order of organo-accumulative soils. The differences between them are related to differences in the types of humus and surface organic horizons. In the case of the low thickness of the profiles, the soils belong to the orders of lithozems and/or poorly developed stony soils (petrozems). As a rule, the same unit in the legend to the map corresponds to two or more soils in the new classification system. The mapping unit “mountainous forest-meadow soils” has been subdivided into five different soils with due account for the regional specificity of soil properties and landscape features. In the course of this study, several suggestions to improve the classification system of Russian soils have been made.